Study of Rna-A Initiation Translation of the Infectious Pancreatic Necrosis Virus - Sandino-Garcia, A; Diaz-Meza, A; González-Catrilelbún, S (Elsevier B.V., 2017)
The infectious pancreatic necrosis virus (IPNV) is a salmonid pathogen that causes significant economic losses to the aquaculture industry. IPNV is a non-enveloped virus containing two uncapped and non-polyadenylated double strand RNA genomic segments, RNA-A and RNA-B. The viral protein Vpg is covalently attached to the 5′ end of both segments. There is little knowledge about its viral cycle, particularly about the translation of the RNAs. Through experiments using mono and bicistronic reporters, in this work we show that the 120-nucleotide-long 5’-UTR of RNA-A contains an internal ribosome entry site (IRES) that functions efficiently both in vitro and in salmon cells. IRES activity is strongly dependent on temperature. Also, the IRES structure is confined to the 5’UTR and is not affected by the viral coding sequence. This is the first report of IRES activity in a fish virus and can give us tools to generate antivirals to attack the virus without affecting fish directly. © 2017
Keywords: Infectious Pancreatic Necrosis Virus; Internal Ribosome Entry Site; Vpg; Salmonids; Fish pathogens